Legal Consequences of Making a Notary's Cover Note in the Implementation of Notary's Duties - Ikhsan Lubis; Tarsisius Murwadji; Sunarmi Sunarmi; Detania Sukarja (SASI, 2023)
Introduction: One of the legal goods provided by a notary is a cover note, which is a statement in the management of a deed or a notarial document stating that the deed is in progress and can be finished within the time set by the cover note.